1999
DOI: 10.1111/1467-9469.00155
|View full text |Cite
|
Sign up to set email alerts
|

Random Bernstein Polynomials

Abstract: Random Bernstein polynomials which are also probability distribution functions on the closed unit interval are studied. The probability law of a Bernstein polynomial so de®ned provides a novel prior on the space of distribution functions on [0, 1], which has full support and can easily select absolutely continuous distribution functions with a continuous and smooth derivative. In particular, the Bernstein polynomial which approximates a Dirichlet process is studied. This may be of interest in Bayesian non-para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 44 publications
0
99
0
Order By: Relevance
“…In this paper we show how a Bayesian nonparametric approach can be implemented in a simple way, using either Pólya tree prior distributions (Ferguson, 1974), or Bernstein polynomial prior distributions (Petrone, 1999a(Petrone, , 1999b. It is also well known that both types support to absolutely-continuous distributions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we show how a Bayesian nonparametric approach can be implemented in a simple way, using either Pólya tree prior distributions (Ferguson, 1974), or Bernstein polynomial prior distributions (Petrone, 1999a(Petrone, , 1999b. It is also well known that both types support to absolutely-continuous distributions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Bernstein polynomial prior distribution, introduced by Petrone (1999aPetrone ( , 1999b, assumes that a univariate random density function f (with sample space domain [0; 1]) has the representation:…”
Section: Model Based On the Bernstein Polynomial Priormentioning
confidence: 99%
“…Using an idea of Diaconis that this approximation property may be exploited to construct priors with full topological support, Petrone (1999aPetrone ( , 1999b proposed the following hierarchical prior called the Bernstein polynomial prior: Petrone (1999a) showed that if for all k, ρ(k) > 0 and w k has full support on ∆ k , then every distribution on (0, 1] is in the weak support of the Bernstein polynomial prior, and every continuous distribution is in the topological support of the prior defined by the Kolmogorov-Smirnov distance.…”
Section: Bernstein Polynomialsmentioning
confidence: 99%
“…, x n ). Petrone (1999aPetrone ( , 1999b discussed MCMC algorithms to compute the posterior expectations and carried out extensive simulations to show that the resulting density estimates work well.…”
Section: Bernstein Polynomialsmentioning
confidence: 99%
“…The importance of the Bernstein polynomials opened the gates to the discovery of their numerous generalizations as well as their applications in various mathematical disciplines, see, for example, [1][2][3][4][5][6][7][8]. Due to the speedy development of the qcalculus, recent generalizations based on the q-integers have emerged.…”
Section: Introductionmentioning
confidence: 99%